Question and Answers Forum

All Questions      Topic List

None Questions

Previous in All Question      Next in All Question      

Previous in None      Next in None      

Question Number 70163 by A8;15: last updated on 01/Oct/19

Answered by ajfour last updated on 01/Oct/19

Commented by ajfour last updated on 02/Oct/19

  ((AB)/(BC))=Q= ((x+y)/(√(y^2 +z^2 )))   x+y+e+d=2c−a      ....(i)  (x/y)=(a/b)   &   (e/d)=(b/c)       ...(ii)    (2c−a)^2 =4ac  ⇒   4((c/a))^2 −8((c/a))+1=0  ⇒  (c/a)=λ=((8+(√(64−16)))/8) =1+((√3)/2)      (e+d)^2 =4bc      d((b/c)+1)=2(√(bc))  ⇒  d=((2c(√(bc)))/(b+c))    ,  e=((2b(√(bc)))/(b+c))   ((a−z)/(z−b))=(a/b)   ⇒  ab−bz=az−ab  ⇒    z=((2ab)/(a+b))     y^2 = b^2 −(z−b)^2          = 2bz−z^2  = ((4ab^2 (a+b)−4a^2 b^2 )/((a+b)^2 ))    y=((2b(√(ab)))/(a+b))    ;   x= ((2a(√(ab)))/(a+b))    Q=((AB)/(BC))=((x+y)/(√(y^2 +z^2 )))        = ((2(√(ab)))/(√((((2b(√(ab)))/(a+b)))^2 +(((2ab)/(a+b)))^2 )))     =((2(a+b)(√(ab)))/(√(4ab^2 (b+a)))) = (√(1+(a/b)))  Now  taking up (i)      x+y+e+d=2c−a     2(√(ab))+2(√(bc))=2c−a  ⇒  2(√(b/a))+2(√(λ((b/a)))) =2λ−1  ⇒ 2(√(b/a))(1+(√λ))=2λ−1     (√(b/a)) = ((2λ−1)/(2(1+(√λ))))  Q= ((AB)/(BC)) = (√(1+((4(1+(√λ))^2 )/((2λ−1)^2 ))))      λ=1+((√3)/2) .

ABBC=Q=x+yy2+z2x+y+e+d=2ca....(i)xy=ab&ed=bc...(ii)(2ca)2=4ac4(ca)28(ca)+1=0ca=λ=8+64168=1+32(e+d)2=4bcd(bc+1)=2bcd=2cbcb+c,e=2bbcb+cazzb=ababbz=azabz=2aba+by2=b2(zb)2=2bzz2=4ab2(a+b)4a2b2(a+b)2y=2baba+b;x=2aaba+bQ=ABBC=x+yy2+z2=2ab(2baba+b)2+(2aba+b)2=2(a+b)ab4ab2(b+a)=1+abNowtakingup(i)x+y+e+d=2ca2ab+2bc=2ca2ba+2λ(ba)=2λ12ba(1+λ)=2λ1ba=2λ12(1+λ)Q=ABBC=1+4(1+λ)2(2λ1)2λ=1+32.

Terms of Service

Privacy Policy

Contact: info@tinkutara.com